2001
DOI: 10.1017/s081406260000241x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Education in Environmental Education – Does it Work?

Abstract: This paper summarises a research project carried out by the author on the effectiveness of pre-service teacher education in environmental education in New Zealand. Secondary pre-service teacher education students who had opted for a 20 hour course in environmental education expressed a high degree of satisfaction with the course but this begged the question of what would happen to them once they hit the reality of the classroom in a country which then had no policy or curriculum guidelines on environmental edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
(2 reference statements)
0
8
0
1
Order By: Relevance
“…Teacher educators provide a range of personal and professional rationales for embedding SE into initial teacher education, but tend to be driven by an overall desire to equip student teachers with the capacity to implement SE in schools. Over half the authors (Bennett & Heafner, 2004;Cheong, 2005;Corney, 2006;Corney & Reid, 2007;Firth & Winter, 2007;Jenkins, 1999Jenkins, /2000Karpudewan et al, 2009;Kennelly & Taylor, 2007;Kennelly et al, 2008;McConnell, 2001;Nicholas et al, 1993;Paige et al, 2008;Phelps et al, 2008;Taylor et al, 2006;Van Petegem et al, 2007;Varga et al, 2007) emphasise the importance of facilitating student teachers to develop the knowledge, understanding, skills and/or values to embed SE into their own teaching practices once in their educational settings. However, given the centrality of values (e.g., intergenerational and intercultural equity) in sustainability discourse, it is significant that values are not always explicitly included in these rationales.…”
Section: What Rationales Are Provided By Teacher Educators For Embedding Se Into Initial Teacher Education?mentioning
confidence: 99%
“…Teacher educators provide a range of personal and professional rationales for embedding SE into initial teacher education, but tend to be driven by an overall desire to equip student teachers with the capacity to implement SE in schools. Over half the authors (Bennett & Heafner, 2004;Cheong, 2005;Corney, 2006;Corney & Reid, 2007;Firth & Winter, 2007;Jenkins, 1999Jenkins, /2000Karpudewan et al, 2009;Kennelly & Taylor, 2007;Kennelly et al, 2008;McConnell, 2001;Nicholas et al, 1993;Paige et al, 2008;Phelps et al, 2008;Taylor et al, 2006;Van Petegem et al, 2007;Varga et al, 2007) emphasise the importance of facilitating student teachers to develop the knowledge, understanding, skills and/or values to embed SE into their own teaching practices once in their educational settings. However, given the centrality of values (e.g., intergenerational and intercultural equity) in sustainability discourse, it is significant that values are not always explicitly included in these rationales.…”
Section: What Rationales Are Provided By Teacher Educators For Embedding Se Into Initial Teacher Education?mentioning
confidence: 99%
“…Higher education institutions are also autonomous in deciding the content of their teaching. For example, if sustainable development or EE are not seen as essential themes in teaching, they do not necessarily have to be implemented [13,[43][44][45][46][47][48]. Therefore, the activities of education organizations must also be viewed critically in the light of entrepreneurship and sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of teacher education has been emphasized, EE still seems to be a moderately overlooked theme in teacher education across our three countries [24,42]. Similarly, while there have clearly been attempts to include environmental education and research ideas in teacher education, these are not yet bearing much fruit -and indeed, a number of studies from around the world suggest that environmental education is not easy to fit into general teacher education programmes [13,[43][44][45][46][47][48]. In summary, research emphasizes that strengthening both EE and sustainable education in teacher education would have more added value than we might think.…”
Section: What Could Be the Opportunities Of Nordic Teacher Education?mentioning
confidence: 99%
“…Problems in the preparation of teachers for environmental education are well documented in the literature (Bowen, 2002;Heimlich et al, 2004;Jenkins, 1999Jenkins, /2000Lane, Wilke, Champeau & Sivek, 1995;McConnell, 2001;McKeown-Ice, 2000;Morgado, 2004;Scott, 1996;Spork, 1992; Working Party on Environmental Education, 1993). As early as 1987, it was noted that "few, if any, teacher training programs adequately prepare teachers to effectively achieve the goals of environmental education in their classrooms" (Wilke, Peyton and Hungerford, 1987;cited in Fien 1993, p. 1).…”
Section: Challenges In the Preparation Of Teachers For Environmental mentioning
confidence: 99%
“…A recent study (Heimlich et al, 2004), exploring how environmental education might be better incorporated into teacher preparation programs in the USA found that the biggest barrier to environmental education content is not a lack of interest, expertise, or relevance but a lack of mandates at the political level. Research on teacher education in New Zealand by McConnell (2001) also reported the need for a change in the political climate recognising the need for environmental education. Part of the problem in teacher education may also be that, many teachers received their education and pre-service training long before interdisciplinary courses in environmental studies were available and before socially transformative approaches to teacher education, which have the potential to empower teachers to work for constructive social change, were developed.…”
Section: Challenges In the Preparation Of Teachers For Environmental mentioning
confidence: 99%